Strategies for interprofessional facilitators and clinical supervisors that may enhance the emotional intelligence of therapy students. Issue 5 (3rd September 2017) - Gribble, Nigel; Ladyshewsky, Richard K.; Parsons, Richard
ABSTRACT: Emotional intelligence (EI) is a critical skill for occupational therapy, physiotherapy, and speech pathology students (therapy students). This article reports the findings from an analysis of interviews with therapy students (n = 24) to determine the aspects of clinical placements that therapy students perceived as influencing the changes in EI scores. This article reports the findings of the qualitative phase of a longitudinal, retrospective mixed methods design. Interviewees were selected using purposive sampling. Of those interviewed, 95% agreed that clinical placements had a significant impact on a range of EI skills with changes being both positive and negative. Content analysis showed that students perceived their EI skills had changed because of the following aspects of clinical placements: student-supervisor interactions, student interactions with patients in emotional distress and being encouraged to reflect and hear feedback on their EI skills. To support and enhance student's EI skills, interprofessional facilitators and profession-specific supervisors are recommended to utilise the following strategies with interprofessional cohorts. Supervisors and facilitators should be emotionally in-tune with students and trust students to work autonomously with patients experiencing emotional distress, pain and loss, especially those with complex needs. Importantly, interprofessional facilitators and direct supervisors should encourage students to reflect on their EI skills both individually and as a group. Supervisors should frequently evaluate and provide feedback to students on their EI skills, at the same time as providing feedback on their practical and clinical reasoning skills.